2010
DOI: 10.1292/jvms.09-0397
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Gene Expression and Enzyme Activity of Hepatic Cytochrome P450 in Juvenile Sprague-Dawley Rats

Abstract: ABSTRACT. The developmental changes in the hepatic cytochrome P450 (CYP) content, mRNA expression of 12 hepatic CYP subtypes, and the enzyme activities of 5 hepatic CYP subfamilies in rats were investigated using non-treated male and female Sprague-Dawley rats of ages postnatal day (PD) 4, 16, 30 and 8 and 12 weeks. The hepatic proliferation kinetics was also determined by using the phospho-histone H3 (p-histon)-labeled hepatocyte index. The developmental changes in the enzyme activities of hepatic expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…To summarize, pharmacokinetics of gentiopicroside and swertiamarin in rats are subject to a gender effect, which could give rise to individual differences in drug efficacy and toxicity if it translates to human. It has been reported that the activity of most CYP enzymes are significantly lower in female rats than in male rats,[21,22] which may explain the gender difference in the pharmacokinetics of gentiopicroside and swertiamarin observed in this study. However, further studies are required to explore the mechanism of this gender effect to better understand the pharmacokinetic profiles of gentiopicroside and swertiamarin.…”
Section: Resultsmentioning
confidence: 53%
“…To summarize, pharmacokinetics of gentiopicroside and swertiamarin in rats are subject to a gender effect, which could give rise to individual differences in drug efficacy and toxicity if it translates to human. It has been reported that the activity of most CYP enzymes are significantly lower in female rats than in male rats,[21,22] which may explain the gender difference in the pharmacokinetics of gentiopicroside and swertiamarin observed in this study. However, further studies are required to explore the mechanism of this gender effect to better understand the pharmacokinetic profiles of gentiopicroside and swertiamarin.…”
Section: Resultsmentioning
confidence: 53%
“…This phenomenon has been reported in all food‐producing animals such as sheep (Kaddouri et al ., ; Flåøyen & Jensen, ; Galtier & Alvinerie, ; Pretheeban et al ., ), cattle (Kawalek & el Said, ), and chicken (Hamilton & Bloom, ; Hamilton et al ., ; Lorr & Bloom, ; Lorr et al ., ; Hu, ). The typical pattern of CYP450 contents and activities for nonselective or overall CYP450 are low at neonates, increase to adults, and decrease to elders in mammals (Tanaka, ; Lupp et al ., ; Asaoka et al ., ). In commercial pork production, the growth phase from neonate to market body weight pigs is of the greatest practical significance, as the vast majority of pigs are raised only until approximately 5 months of age.…”
Section: Discussionmentioning
confidence: 97%
“…Briefly, earlier reports demonstrate that CYP2B1/2 and CYP3A2 expression and activities are lower in female rats, whereas no sex specific differences are observed for CYP1A2 (Asaoka et al, 2010). Furthermore, treatment with PB results primarily in an induction of CYP2B1 on both male and female rats (Waxman et al, 1985; Lee et al, 1992; Nims et al., 1993), whereas treatment with DEX induces CYP3A2 and CYP2B1 (Choudhuri et al, 1995; Meredith et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with rat CYP2B1 and human CYP2B6 enzymes (Warner et al, 2009) and hepatic microsomes (Wu et al, 2011) demonstrate that chiral PCBs are enantioselectively metabolized to OH-PCBs by P450 enzymes. Expression and activity of CYP2B1 displays sex specific differences (Asaoka et al, 2010) and is inducible by a range of xenobiotics (Waxman and Walsh, 1982; Meredith et al, 2003). Similarly, the human orthologue, CYP2B6, is a highly inducible enzyme that may display sex specific differences in expression and activities (Zanger et al., 2007).…”
Section: Introductionmentioning
confidence: 99%